1997
DOI: 10.1159/000237644
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity of Recombinant Der p 2, Der p 5 and Der p 7 Allergens of the House-Dust Mite <i>Dermatophagoides pteronyssinus</i>

Abstract: Der p 2, Der p 5 and Der p 7 are three allergens of the house-dust mite Dermatophagoides pteronyssinus that have been cloned and expressed in Escherichia coli as fusion proteins with glutathione-S-transferase (GST). We showed that these recombinant allergens produced immediate hypersensitivity skin-test reactions in 70, 60 and 52% respectively of a group of mite-sensitive allergic patients who were strongly positive to whole mite extract (WME). Comparable positiv-ities were found for serum levels of specific I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 16 publications
2
38
0
Order By: Relevance
“…On the other hand, group 2 allergens including Der p 2 of D. pteronyssinus , Lep d 2 from Lepidoglyphus destructor, Der f 2 from D. farinae [94]and Tyr p 2 from Tyrophagus putrescentiae , have been evaluated in skin tests. Group 2 allergens, although not yet defined in terms of biological function, are recognized by the majority of the mite-sensitized allergics [95, 96, 97, 98, 99]. Unfortunately, group 5 and group 7 allergens could also not be assigned to a functional class of proteins with the exception of their ability to bind IgE from sensitized individuals [36].…”
Section: The Potential or Rallergens For Diagnostic Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, group 2 allergens including Der p 2 of D. pteronyssinus , Lep d 2 from Lepidoglyphus destructor, Der f 2 from D. farinae [94]and Tyr p 2 from Tyrophagus putrescentiae , have been evaluated in skin tests. Group 2 allergens, although not yet defined in terms of biological function, are recognized by the majority of the mite-sensitized allergics [95, 96, 97, 98, 99]. Unfortunately, group 5 and group 7 allergens could also not be assigned to a functional class of proteins with the exception of their ability to bind IgE from sensitized individuals [36].…”
Section: The Potential or Rallergens For Diagnostic Applicationmentioning
confidence: 99%
“…Unfortunately, group 5 and group 7 allergens could also not be assigned to a functional class of proteins with the exception of their ability to bind IgE from sensitized individuals [36]. rDer p 5 and rDer p 7 from D. pteronyssinus and Blo t 5 from Blomia tropicalis have been confirmed to be able to elicit type 1 reactions in clinical studies [95, 96, 97, 98, 100, 101]. However, in view of the shared sequence homology, members of a distinct group of structurally related allergens can be expected to be cross-reactive as demonstrated in vitro for some of the mite allergens [102].…”
Section: The Potential or Rallergens For Diagnostic Applicationmentioning
confidence: 99%
“…allergens group 1 and 2 allergens seem to be the most important ones, as (i) they are recognized by ∼70–100% of HDM-sensitized patients [2,13,14,15,16,17,18,19,20,21,22,23]; (ii) they bind substantial amounts of anti-mite IgE (i.e. 30–40% each on average) in patients’ sera [15,19,20,21, 24]. A recent study demonstrated that a mixture of group 1, 2, 5, 7, 8 and 10 allergens binds an average of 76% of D. pteronyssinus -specific IgE [25].…”
Section: Introductionmentioning
confidence: 99%
“…More than 90% of patients with AD are positive for the IgE radioallergosorbent test (IgE-RAST) against mite Ag [9], and clinical symptoms of AD improved after mites had been removed [10, 11]. Dermatophagoides pteronyssinus (Dp), a representative allergen of human AD, is involved in the pathogenesis of AD [12]. Although mite Ag are major allergens in human AD, there is no suitable animal model for investigating the importance of mite Ag in AD.…”
Section: Introductionmentioning
confidence: 99%